Community Perspectives on Primary Prevention of Rheumatic Heart Disease in Uganda. Issue 1 (20th January 2022) - Nalubwama, Hadija; Ndagire, Emma; Sarnacki, Rachel; Atala, Jenifer; Beaton, Andrea; Kansiime, Rosemary; Mwima, Rachel; Okello, Emmy; Watkins, David
Background: Untreated streptococcal pharyngitis is a precursor to rheumatic heart disease (RHD) and remains a significant public health issue in many countries. Understanding local determinants of treatment-seeking behaviors can help tailor RHD prevention programs. Objective: We sought to elicit perceptions of pharyngitis and related healthcare use in a range of communities in Uganda. Methods: We conducted six focus group discussions (FGD) in three districts that were representative of the country's socioeconomic and cultural heterogenetity. Participants were recruited from six villages (two per district), and FGDs were audio recorded, transcribed and translated into English. Deductive and inductive analysis of the transcripts was done via open axial and sequential coding, which informed development of clusters, themes and subthemes. We extracted quotations from the transcripts to illustrate these themes. Results: We identified nine key themes in three major domains: knowledge and perception of pharyngits, treatment practices, and barriers to uptake of formal public-sector healthcare services. Community awareness and understanding of the consequences of pharyngitis were low. Stated barriers to care were usually systemic in nature and included low overall confidence in the healthcare system and substantial costs associated with transportation and medications. Conclusion: The FGDs identified several approaches to shape community perceptions of pharyngitis and improve utilization of interventions to prevent RHD. In Uganda, information-education-communication interventions probably need to be combined with structural interventions that make formal public-sector healthcare more accessible to at-risk populations.